The Development of CNC Hot Wire 3D Cutting Foam Tool - Sugeng Dwi Riyanto; Saepul Rahmat; Muhammad yusuf (Jurnal Jaringan Telekomunikasi, 2023)
Wedding decorations are considered incomplete without decoration. The decoration business must prepare a skilled and creative workforce and improve the artistic creation skills of employees to provide several choices of decorating styles to clients. The material that was recently used in decorations is styrofoam. The purpose of this research is to design a CNC machine to get good results and neatly cut Styrofoam using a hot wire. This research also contributes to solving problems with Styrofoam cutting usually a problem with detailed and complicated work that can be solved automatically using a CNC machine. Tool hardware design requires Bluetooth connection, driver to the stepper motor, driver A4988 to CNC shield, and step down to the heating wire. Software design includes uploading GRBL firmware, creating G-code using Inkscape Software, and connecting Android applications to CNC machines. The result shows that for 2-dimensional styrofoam cutting with 1cm thickness, the best results are obtained in the range voltage of 7.4-8.5V. Styrofoam also testing is carried out using the same voltage 8.5V but with different feed rates and the result with 400 mm/min shows the best cut performance. The results of cutting 3-dimensional Styrofoam showed that for a voltage of 8.5V, a feed rate of 300mm/min, and a thickness of 10cm Styrofoam produced the best cutting texture from others. This shows that the heat generated by the wire is directly proportional to the feed rate